The Impact of Workplace and Personal Superannuation Schemes on Net Worth: Evidence from the Household Savings Survey - Grant M Scobie; Trinh Le (New Zealand Government, The Treasury, 2004)
The central question addressed in this paper is: does having a workplace or personal superannuation scheme result in a higher level of accumulation for retirement? The paper presents a range of information about the participation and level of holdings in workplace and personal superannuation schemes based on data from the Household Saving Survey (HSS). While the proportion of people holding a scheme is small (around 10%), the value of a scheme for those enrolled represents about one third their total net worth. There is evidence that being enrolled in a workplace scheme is associated with higher levels of total net worth, yet this is not true of personal schemes, once several personal characteristics have been controlled for. Nevertheless, it is evident that those in either workplace schemes or personal have not fully substituted this form of saving for other vehicles. In fact in all cases there appears to be complementarity, whereby higher holdings in a scheme are associated with higher holdings in other forms of savings. Typically, an additional dollar invested in a workplace scheme is associated with higher total net worth of between one and two dollars, while for personal schemes the figure typically exceeds two dollars. Two possible explanations for this arise. The first is that by enrolling in a scheme an individual acquires heightened awareness of the importance of retirement saving and saves additional amounts in other vehicles. An alternative hypothesis is that there may be some self-selection bias; those who have enrolled might be more inclined to save than the population as a whole. There is no direct way to use the data to discriminate between these two possibilities. However holding constant a wide range of other factors (including age, income, ethnicity, residence, etc) it is reasonable to suppose that the more likely sources of selection bias may have been controlled for. If this is the case then the finding that more holdings of workplace superannuation are associated with greater total retirement wealth may well have arisen from an "awareness" or "recognition" effect of belonging to a scheme. In this event, policies which foster enrolment might lead to greater retirement accumulation by those in a scheme.
Keywords: J26; 330; Superannuation; Retirement; New Zealand; Net Worth: Saving; Household Behaviour